2013
DOI: 10.1002/jnr.23318
|View full text |Cite
|
Sign up to set email alerts
|

5‐S‐cysteinyldopamine neurotoxicity: Influence on the expression of α‐synuclein and ERp57 in cellular and animal models of Parkinson's disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder whose etiology is still unclear in spite of extensive investigations. It has been hypothesized that 5-S-cysteinyldopamine (CysDA), a catechol-thioether metabolite of dopamine (DA), could be an endogenous parkinsonian neurotoxin. To gain further insight into its role in the neurodegenerative process, both CD1 mice and SH-SY5Y neuroblastoma cells were treated with CysDA, and the data were compared with those obtained by the use of 6-hydroxydopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 74 publications
(97 reference statements)
0
29
0
1
Order By: Relevance
“…Conversely, catecholamine metabolites, such as 5-S-Cysteinyldopamine, modulate α-syn expression through oxidative stress (Aureli et al, 2014). Thus, reserpine-induced increases in catecholamine metabolites and oxidative imbalances may be in the core of the neurochemical alterations reported here (Leão et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, catecholamine metabolites, such as 5-S-Cysteinyldopamine, modulate α-syn expression through oxidative stress (Aureli et al, 2014). Thus, reserpine-induced increases in catecholamine metabolites and oxidative imbalances may be in the core of the neurochemical alterations reported here (Leão et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[ 51,52 ] Identity and purity of the compound was secured by comparison with literature data. [ 34 ] pDA and pCDA were prepared by autoxidation of DA or CDA in 0.05 M NH 3 buffer, pH 8.5 at 10 mM fi nal concentration according to Bernsmann et al [ 53 ] After 24 hours under vigorous stirring, the reaction mixture was acidifi ed to pH 2 with 3M HCl and the pigment that separated was collected by centrifugation at 7000 rpm at 4 °C, washed 3 times with slightly acidic water and lyophilized for 12 hours.…”
Section: Methodsmentioning
confidence: 99%
“…,b; Aureli et al . ). Current treatments such as dopaminergic replacement therapy have been proposed to alleviate some of the symptoms of PD, but there are no existing therapies that can rescue any of the underlying pathological conditions of PD (Calne et al .…”
Section: Changes In the Endocannabinoid System In Neurodegenerative Dmentioning
confidence: 97%
“…For instance, inflammation through activation of microglia in the SN (McGeer et al 1988) and an increase in TNF-a, IL-1b, IL-2, IL-4, and IL-6 (Ouchi et al 2005;Gerhard et al 2006;Taylor et al 2013), have been suggested to be significant pathogenic factors in sporadic PD, in which they lead to loss of dopaminergic (DA) neurons in the SN and thus to the DA denervation in the striatum. Missense mutations in the asynuclein (a-syn) gene have been shown to cause autosomal dominant familial PD (Polymeropoulos et al 1997;Kruger et al 1998;Zarranz et al 2004), and it has been suggested that a-syn causes the microglia-mediated inflammatory response in PD (Zhang et al 2005;Austin et al 2006;Thomas et al 2007;Gao et al 2008;Klegeris et al 2008;Reynolds et al 2008a,b;Aureli et al 2014). Current treatments such as dopaminergic replacement therapy have been proposed to alleviate some of the symptoms of PD, but there are no existing therapies that can rescue any of the underlying pathological conditions of PD (Calne et al 2005;Trapani et al 2011;Denora et al 2012;Di Gioia et al 2015).…”
Section: Ec System In Parkinson's Diseasementioning
confidence: 99%